Case report: Achieving significant tumor reduction in advanced pancreatic adenocarcinoma - Hongying Liu; Yun Wang; Qian Zhang; Nengwen Ke (Frontiers in Oncology)
Pancreatic cancer remains a highly malignant and challenging tumor with a dismal 5-year survival rate of only 13%. The majority of patients are diagnosed at advanced stages, where surgical options are limited, and prognosis is poor. Immunotherapy, particularly PD-1 inhibitors, has shown limited success in pancreatic cancer due to its unique tumor immune microenvironment. However, certain genetic profiles, such as BRCA1/2 mutations, high tumor mutational burden (TMB), or microsatellite instability-high (MSI-H), may enhance sensitivity to these therapies. This report presents two cases of advanced pancreatic cancer with BRCA1/2 mutations treated with a combination of chemotherapy and immune checkpoint inhibitors. The first patient, with TMB-H and stable microsatellites, achieved complete remission after conversion therapy and remains disease-free for over two years post-surgery. The second patient, with MSI-H and low TMB, experienced significant tumor regression and improved quality of life with a prolonged progression-free survival, although the patient ultimately declined surgery. These cases suggest that combined chemotherapy and immunotherapy may offer a promising treatment option for select pancreatic cancer patients, particularly those with specific genetic profiles, warranting further investigation into personalized approaches to immunotherapy in this malignancy.